2021
DOI: 10.1002/jmri.27768
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Left Atrial Strain and Strain Rate Based on a Large Sample of Healthy Chinese Adults: An MR‐Feature Tracking Study

Abstract: Background While reference values of left atrial (LA) deformation parameters in Western populations have been established, reference data in healthy Asian populations are limited. Purpose To establish age‐ and sex‐specific reference values for LA strain and strain rate (SR) based on a large sample of healthy Chinese adults using magnetic resonance‐feature tracking (MR‐FT). Study Type Retrospective. Population Four hundred and eight healthy Chinese adults (220 males, aged 43.5 ± 11.5 years; 188 females, aged 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…30 However, previous studies about the effect of sex on LA strain parameters were not always consistent. Gao et al 12 found that women had higher magnitudes of LA strain and strain rate than men in a cohort of healthy Chinese adults, Liao et al 31 also reached a similar conclusion with a large Asian population. Truong et al 32 demonstrated that LA strain and strain rate were similar between both genders using CMR-FT. Age, sample size, and race may together partially explain the inconsistency of our results with previous studies.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…30 However, previous studies about the effect of sex on LA strain parameters were not always consistent. Gao et al 12 found that women had higher magnitudes of LA strain and strain rate than men in a cohort of healthy Chinese adults, Liao et al 31 also reached a similar conclusion with a large Asian population. Truong et al 32 demonstrated that LA strain and strain rate were similar between both genders using CMR-FT. Age, sample size, and race may together partially explain the inconsistency of our results with previous studies.…”
Section: Discussionmentioning
confidence: 72%
“…7 Although both men and women have similar mechanisms that regulate arterial blood pressure, sex-specific differences indeed exist in prevalence and treatment response following cardiovascular adverse events. 8 Previous studies have demonstrated the influence of sex on LV strain in a healthy population free of cardiovascular disease and patients with hypertension by cardiac magnetic resonance feature tracking (CMR-FT) [9][10][11] and also observed that women had a significantly higher LA strain and strain rate than men based on a large sample of healthy Chinese adults using CMR-FT, 12 whereas study on the sex-related differences of LA strain in hypertension is scarce and the potential mechanism remains unclear. The CMR-FT technique, with better spatial resolution and reproducibility, has been increasingly recognized as an accurate and feasible technique for evaluating LA strain and strain rate, superior to speckle tracking echocardiography.…”
mentioning
confidence: 99%
“…Stability and repeatability are advantageous [ 11 ]. More crucially, several CMR-FT investigations [ 12 , 13 ] on LA strain and strain rate (SR) have demonstrated high inter-and intraobserver repeatability.…”
Section: Introductionmentioning
confidence: 99%